2014
DOI: 10.1016/j.jaip.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Drug Allergy Educational Program and Antibiotic Prescribing Guideline on Inpatient Clinical Providers’ Antibiotic Prescribing Knowledge

Abstract: Background Inpatient providers have varying levels of knowledge in managing patients with drug and/or penicillin (PCN) allergy. Objectives Our objectives were: 1) to survey inpatient providers to ascertain their baseline drug allergy knowledge and preparedness in caring for patients with PCN allergy and 2) to assess the impact of an educational program paired with the implementation of a hospital-based clinical guideline. Methods We electronically surveyed 521 inpatient providers at a tertiary care medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 31 publications
1
74
0
Order By: Relevance
“…Although not addressed in this survey, applying this evidence into clinical practice may help effect change in these common clinicial scenarios [18]. More encouragingly, Blumenthal et al [6] demonstrated that clinician practices could be altered with decision support and a guided education program.…”
Section: Discussionmentioning
confidence: 99%
“…Although not addressed in this survey, applying this evidence into clinical practice may help effect change in these common clinicial scenarios [18]. More encouragingly, Blumenthal et al [6] demonstrated that clinician practices could be altered with decision support and a guided education program.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also documented a lack of understanding of drug allergy among physicians 78 and poor treatment and low referral for drug allergy testing from the emergency department, 79 whereas another study showed how educational interventions could improve a physician's understanding of drug allergy. 80 Several studies addressed drug allergy testing. 81 Fox and Park 82 suggested the safety and efficacy of penicillin skin testing.…”
Section: Drug Allergymentioning
confidence: 99%
“…Several mechanisms of action have been proposed for the anti-inflammatory efficacy of antibiotics and traditional Chinese medicines (TCMs) on respiratory diseases, including COPD, house dust mite-induced allergic asthma, resistance of Klebsiella pneumoniae, and ventilator-associated pneumonia (12)(13)(14)(15). However, the efficacy of such antibiotics was limited by their side effects in clinical trials, which included vomiting, diarrhea, weight loss and headaches (16)(17)(18). At present, no effective control measures have been developed for the treatment of PM 2.5 -induced respiratory diseases apart from reducing PM 2.5 emissions, wearing a dust respirator and increasing the number of plants.…”
Section: Introductionmentioning
confidence: 99%